(untitled) (World Bulletin of Education and Learning, 2025)
The article examines the pedagogical significance of using modern information and multimedia technologies in the education system, particularly electronic educational resources and multimedia presentations. The role of multimedia tools in enhancing the effectiveness of understanding and mastering learning materials in primary school mathematics lessons is analyzed. The study highlights the possibilities of activating students’ cognitive activity, expanding opportunities for individualized learning, and improving the didactic effectiveness of the educational process through slides prepared on the basis of electronic teaching aids, animation, and visual effects. Practical approaches to the application of multimedia technologies are demonstrated using examples of exercises developed with the PowerPoint software.